Effects of alpha lipoic acid on acrylamide-induced hepatotoxicity in rats - Al-Qahtani, F. A.; Arafah, M.; Sharma, B.; Siddiqi, N. J. (Cellular and Molecular Biology, 2017)
Acrylamide (ACR) is a neurotoxicant, reproductive toxicant, and carcinogen in animal species.  It is used in many industries and has been found to form naturally in foods cooked at high temperatures. Alpha-lipoic acid (ALA) is a naturally occurring antioxidant whose therapeutic effect has been related to its antioxidant activity.  This study was carried out to study the protective effect of alpha lipoic acid on acrylamide induced perturbations in rat liver.  Four groups of rats were studied viz., control rats, acrylamide treated rats, alpha lipoic acid treated rats, and alpha lipoic acid plus acrylamide treated rats. ACR and ALA treatment alone and together caused a significant increase in hepatic reduced glutathione content while a decrease in hepatic ascorbic content was observed when compared to control group.  ALA pretreatment of acrylamide exposed rats caused no a significant alteration in superoxide dismutase activity but resulted in a tendency towards restoration of glutathione peroxidase and catalase activity to near normal levels.  Gel electrophoresis showed fragmentation of DNA in the treated groups.  The dose of ALA used in the present study afforded partial restoration of oxidative indices altered by ACR in rat liver.